2019
DOI: 10.1097/sla.0000000000002990
|View full text |Cite
|
Sign up to set email alerts
|

US FDA Breast Implant Postapproval Studies

Abstract: Objective: To analyze the long-term safety and efficacy outcomes of patients with breast implants. Summary Background Data: Research is ongoing regarding the safety of silicone breast implants. Despite the number of patients with breast implants followed by United States Food and Drug Administration large postapproval studies (LPAS), this database has not been thoroughly analyzed or reported. Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(108 citation statements)
references
References 55 publications
1
102
0
5
Order By: Relevance
“…The association between silicone breast implants and autoimmune diseases still remains inconclusive considering data from systematic reviews and meta-analyses [ 80 , 81 , 82 ]. A more recent post-approval long-term outcome study on an extremely large cohort suggests that there are higher rates of SS and other autoimmune disorders in patients undergoing silicone breast implants [ 83 ]. This is consistent with case reports dating back 1984 and with the several case series reported over time [ 84 ].…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…The association between silicone breast implants and autoimmune diseases still remains inconclusive considering data from systematic reviews and meta-analyses [ 80 , 81 , 82 ]. A more recent post-approval long-term outcome study on an extremely large cohort suggests that there are higher rates of SS and other autoimmune disorders in patients undergoing silicone breast implants [ 83 ]. This is consistent with case reports dating back 1984 and with the several case series reported over time [ 84 ].…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…The most common complications are contracture and capsule formation, which occur in about ten percent of cases. 9 , 10 Since the 1960s several cases have been reported associating breast implants to systemic diseases. Several literature reviews have been done in this concern, yet no scientific based evidence has been found.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, there are no recommendations or policies for surveillance or optimal follow-up of patients with breast implants. 8 Here we detail the results of patient reporting, diagnosis, and follow-up of patients diagnosed with BIA-ALCL in Colombia through the development of a national registry and the multidisciplinary participation of medical society physicians who may encounter patients with BIA-ALCL in their practices.…”
Section: Discussionmentioning
confidence: 99%